SURGICAL TECHNIQUE FOR COMPLEX SYNDACTYLY IN APERT SYNDROME: A SERIAL CASE - Mesang, Williams; Budi, Agus Santoso; Hutagalung, Magda Rosalina (Universitas Airlangga, 2019)
Highlights: Complex syndactyly in Apert syndrome, particularly when complicated with synonychia and synostosis, poses a significant surgical challenge. Successful surgical techniques for Apert syndrome syndactyly are crucial to achieving these goals. Abstract: Introduction: Complex syndactyly in Apert syndrome, especially complicated with synonychia and synostosis, is a surgical challenge. The incidence of Apert Syndrome is reported to be approximately 1 per 100,000 to 160,000 live births and its incidence in Indonesia is not yet known. It is practically symmetrical causing significant dysfunction and infection if not treated properly. The goals in the treatment are the separation of independent digits without disturbing function and growth, the creation of a lined commissure, the provision of skin cover for the denuded nail edge and exposed bone, and to creation of aesthetically pleasing individual fingertips with proper nails, nail folds, and adequate pulp fullness. This is due to the unreliability of the vascular branching pattern to the digits. Case Illustration: In this serial case, we reported 5 cases of Apert syndrome. We described the clinical findings, incision design, immediate and post-surgery follow-ups. Discussion: In this case, we combined dorsal rectangular flap and palmar triangular flap to make a new web space, Buck Gramcko pulp flap for the nail fold reconstruction, and full thickness skin graft w was taken from the groin to cover the raw areas. Absorbable 5.0 simple interrupted sutures were used in each patient. The results were uneventful, with satisfying function and aesthetic appearance. Conclusion: Choosing the best surgical technique for releasing the web space in syndactyly depends on the patient's condition and the plastic surgeon's decision was needed. In 5 patients, up there was no meaningful complication attained from the postoperative result.